REMEDIASI MISKONSEPSI SISWA MENGGUNAKAN MODEL PEMBELAJARAN CLIS BERBANTUAN MIND MAP PADA MATERI PEMANTULAN CAHAYA - Rasu, Avant Patria; Djudin, Tomo; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to investigate the effectiveness of CLIS learning model with Mind Map to remediate student’s misconception on ‘reflection of light’ for grade VIII students of MTsN 2 Pontianak. The method used in this research was pre-experimenal design with one group pre test Post-test design. The tool of data collection was reasonable mutiple choice test with three answer choices. The sample of this research was 37 students of VIII J class, the sample was chosen using Intact group technique. The average range of students misconception in pre test was 93.3% and in post test was 24%. The average range decreases 69.9% after the treatment. Technique of data analysis using McNemar test showed x2count (97.01) > x2table (3.84). There was conceptual changes significantly after the remediation using CLIS model learning with Mind Map in the material ‘reflection of light’. The effectiveness of remediation obtained from proportion average value where was 0.71 (high). Therefore, teachers suggested to used CLIS learning model as alternative learning technique in order to straighten out students misconception in the material ‘reflection of light’.Keywords: Misconception, CLIS, Mind Map, Reflection of Light